Genome-Wide Association Analysis of Neonatal White Matter Microstructure. (3rd October 2020) - Zhang, J; Xia, K; Ahn, M; Jha, S C; Blanchett, R; Crowley, J J; Szatkiewicz, J P; Zou, F; Zhu, H; Styner, M; Gilmore, J H; Knickmeyer, R C
ABSTRACT: A better understanding of genetic influences on early white matter development could significantly advance our understanding of neurological and psychiatric conditions characterized by altered integrity of axonal pathways. We conducted a genome-wide association study (GWAS) of diffusion tensor imaging (DTI) phenotypes in 471 neonates. We used a hierarchical functional principal regression model (HFPRM) to perform joint analysis of 44 fiber bundles. HFPRM revealed a latent measure of white matter microstructure that explained approximately 50% of variation in our tractography-based measures and accounted for a large proportion of heritable variation in each individual bundle. An intronic SNP in PSMF1 on chromosome 20 exceeded the conventional GWAS threshold of 5 x 10 −8 (p = 4.61 x 10 −8 ). Additional loci nearing genome-wide significance were located near genes with known roles in axon growth and guidance, fasciculation, and myelination.